1995
DOI: 10.1037/0022-3514.69.5.851
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting the subjective well-being of nations.

Abstract: Subjective well-being (SWB) in 55 nations, reported in probability surveys and a large college student sample, was correlated with social, economic, and cultural characteristics of the nations. The SWB surveys, representing nations that include three fourths of the earth's population, showed strong convergence. Separate measures of the predictor variables also converged and formed scales with high reliability, with the exception of the comparison variables. High income, individualism, human rights, and societa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

53
798
5
54

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,341 publications
(910 citation statements)
references
References 18 publications
53
798
5
54
Order By: Relevance
“…This limits any conclusions drawn from these data to a Chilean context. There are fairly well-established national variations in some wellbeing indicators (e.g., life satisfaction ratings, Diener, Diener, & Diener, 1995), and it is important to establish whether these variations obtain for the range of indicators in the present module. Future research also should begin providing information about relationships among the psychological wellbeing components and outcomes of interest, such as health, mortality, education, income poverty, and other socioeconomic factors.…”
Section: Discussionmentioning
confidence: 99%
“…This limits any conclusions drawn from these data to a Chilean context. There are fairly well-established national variations in some wellbeing indicators (e.g., life satisfaction ratings, Diener, Diener, & Diener, 1995), and it is important to establish whether these variations obtain for the range of indicators in the present module. Future research also should begin providing information about relationships among the psychological wellbeing components and outcomes of interest, such as health, mortality, education, income poverty, and other socioeconomic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Individualistic cultures have been found to be generally happier than collectivistic ones (e.g., Diener et al 1995), partly because they provide their members with more personal freedom and autonomy (Inglehart 2000). In sum, we control for positive and negative affect, personal growth initiative, and national individualism to examine if fragility of happiness contributes significantly in the prediction of life satisfaction.…”
Section: Predictive Validitymentioning
confidence: 99%
“…Other research supporting the correlation between increased wellbeing and freedom in general includes Heylighen (1999), Brooks (2008aBrooks ( , 2008b, and (Veenhoven, , 2012. More specifically, Diener, Diener, and Diener (1995) found that political freedom and civil liberties enhance wellbeing, while found that economic freedom augments wellbeing.…”
Section: Freedommentioning
confidence: 99%